Frequency of Different Metoboloic Abnormalities in Paediatric Age Group with Renal Stone Diseases - Abdul Aziz, Akhter Nawaz, Naveed Sultan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Up to 15% of children under the age of 15 may have paediatric urolithiasis, which is linked with severe morbidity and high recurrence rates. This condition is still a serious urological concern. In 86% to 96.1% of kids with kidney stone disorders, metabolic abnormalities are one of the most frequent causes of urolithiasis. Hypercalciuria, hyperoxaluria, hyperuricosurea, and hypocitraturea are the most prevalent metabolic disorders. In order to treat and prevent renal stones in children with renal stone disorders, it is crucial to identify several metabolic abnormalities. Materials and Methods: Descriptive Cross-Sectional Study at the IKD, HMC, Urology Department. This research covered paediatric patients with urolithiasis under the age of 15 years. All patients with urolithiasis had a 24-hour urine assay for metabolic abnormalities on their first visit. Results: 119 individuals, or 72.12%, of the total 165 patients, exhibited metabolic disorders. Out of 119 patients, hypercalciurea affected 56 patients (47.05%), hypocitraturea affected 31 patients (26.05%), hyperoxalurea affected 18 patients (15.12%), and hyperuricosurea affected 14 patients (11.65%). 41 patients, or 34.45% of the 119 total patients, were female youngsters, making up 78 patients (65.54%). The most frequent findings were hypocitraturea and hypercalciuria. Conclusion: Urolithiasis in children is often brought on by metabolic disorders, which are curable and avoidable. In order to detect, treat, and prevent urolithiasis recurrence as well as morbidities brought on by urolithiasis in paediatric patients, it is advised that all paediatric patients presenting with urolithiasis for the first time undergo extensive investigation. Keywords: Metabolic Abnormalities, Recurrent Renal Stones, Urolithiasis